Selective contacts and fill factor limitations in heterojunction solar cells. (18th May 2021) - Serenelli, Luca; Martini, Luca; Menchini, Francesca; Izzi, Massimo; de Cesare, Giampiero; Condorelli, Giuseppe; Gerardi, Cosimo; Muñoz, Delfina; Tucci, Mario
Abstract: Crystalline silicon‐based heterojunction (HJ) solar cells are becoming the best choice for manufacturing companies, because of the low temperature processes useful for very thin silicon wafers and the possibility to easily achieve cells efficiencies higher than 22% on n‐type silicon wafers. However, the maximum cell efficiency is still limited by the typical Fill Factor (FF) value of 82%. This issue is due to several factors, some of which are sometimes underestimated, like the base contact. Indeed, a potential mismatch between the work functions of the transparent conductive oxide and the base doped layer can give rise to a small barrier against electrons collection, which is not easy to recognize when the cell FF overcomes 80%. Also a low doping efficiency of the p‐type amorphous layer at the emitter side can negatively affect the FF. In this case, even if high efficiency cells are produced, their full potential is still unexploited. Thus, both selective contacts of the cell, even if apparently optimized to achieve very good results, can hide problems that limit the final cell FF and efficiency. In a previous work, an experimental method and a model to individuate hidden barriers at the base contact on n‐type crystalline silicon‐based HJs have been provided. In this paper, that model is applied to experimental data obtained from the characterization of both commercial and laboratory level HJ solar cells. Moreover, an easy method to recognize the presence of a barrier to the charge transport at the emitter side of the cell is illustrated. Abstract : Emitter and base selective contacts of heterojunction solar cells are investigated as possible causes for Fill Factor (FF) limitations below 85%. The base contact can introduce a barrier depending on the Transparent Conductive Oxide work function, and a method to indirectly determine this value is presented. Barriers on the emitter contact can be revealed by the appearance of an S‐shape on the J–V characteristics at low temperatures, which is shown to reduce also the cell FF.